How big is big enough? Surprising responses of a semiarid grassland to increasing deluge size. (23rd December 2020) - Post, Alison K.; Knapp, Alan K.
Abstract: Climate change has intensified the hydrologic cycle globally, increasing the magnitude and frequency of large precipitation events, or deluges. Dryland ecosystems are expected to be particularly responsive to increases in deluge size, as their ecological processes are largely dependent on distinct soil moisture pulses. To better understand how increasing deluge size will affect ecosystem function, we conducted a field experiment in a native semiarid shortgrass steppe (Colorado, USA). We quantified ecological responses to a range of deluge sizes, from moderate to extreme, with the goal of identifying response patterns and thresholds beyond which ecological processes would not increase further (saturate). Using a replicated regression approach, we imposed single deluges that ranged in size from 20 to 120 mm (82.3rd to >99.9th percentile of historical event size) on undisturbed grassland plots. We quantified pre‐ and postdeluge responses in soil moisture, soil respiration, and canopy greenness, as well as leaf water potential, growth, and flowering of the dominant grass species ( Bouteloua gracilis ). We also measured end of season above‐ and belowground net primary production (ANPP, BNPP). As expected, this water‐limited ecosystem responded strongly to the applied deluges, but surprisingly, most variables increased linearly with deluge size. We found little evidence for response thresholds within the range of deluge sizes imposed, at least during this dry year. Instead, response patterns reflected the linear increase in the duration of elevated soil moisture (2–22 days) with increasing event size. Flowering of B. gracilis and soil respiration responded particularly strongly to deluge size (14‐ and 4‐fold increases, respectively), as did ANPP and BNPP (~60% increase for both). Overall, our results suggest that this semiarid grassland will respond positively and linearly to predicted increases in deluge size, and that event sizes may need to exceed historical magnitudes, or occur during wet years, before responses saturate. Abstract : Climate change is increasing the magnitude and frequency of large rain events, or deluges. In order to determine the impact of deluge size on key ecological processes in a semiarid ecosystem, we applied single deluges of varying size (82.3rd to >99.9th percentile of historical event size) to grassland plots. Surprisingly, almost all ecosystem processes (i.e. soil respiration, plant production, flowering) increased linearly with deluge size, with limited evidence of response saturation. This suggests that semiarid ecosystems could be well‐adapted to future shifts in precipitation pattern, with consequences for both local ecosystem services and global carbon uptake.